The Effect of Inflation, US Dollar Exchange Rates, Interest Rates, and World Oil Prices on Gold Price Fluctuations in Indonesia 2014 – 2019 - Ummi Kalsum; Randy Hidayat; Sheila Oktaviani (Journal of Business and Management Review, 2020)
This study aims to determine the effect of inflation, US dollar exchange rates, interest rates, and world oil prices on fluctuations in gold prices in Indonesia in 2014 - 2019. This research is a type of explanatory research with a quantitative approach. The data used are monthly time series data for 2014 - 2019 with a sample of 72 samples. The multiple linear regression model is used as an analysis technique in this study. The results of this study indicate that simultaneously (F test) inflation, USD exchange rates, interest rates, and world oil prices have a significant effect on gold price fluctuations in Indonesia. Partially (t-test) shows that the USD exchange rate has a significant positive effect on gold price fluctuations in Indonesia. Inflation and interest rates have a negative and insignificant effect on fluctuations in gold prices in Indonesia. Meanwhile, world oil prices have a positive and insignificant effect on gold price fluctuations in Indonesia.